Alcohol Intoxication Reduces Systemic Interleukin-6 Levels and Leukocyte Counts After Severe TBI Compared With Not Intoxicated TBI Patients. Issue 3 (September 2016) - Wagner, Nils; Akbarpour, Annahita; Mörs, Katharina; Voth, Maika; Störmann, Philipp; Auner, Birgit; Lehnert, Mark; Marzi, Ingo; Relja, Borna
ABSTRACT: Background: The effect of alcohol consumption on inflammatory state and outcome in brain-injured patients remains controversial. We analyzed the influence of positive blood alcohol concentration (BAC) on inflammatory changes, inhospital complications, and mortality in traumatic brain injury (TBI) patients. Patients and Methods: Patients with an Injury Severity Score (ISS) at least 16 and Abbreviated Injury Scale of head (AIS-head) at least 3 were included upon arrival in the emergency room and grouped according to positive BAC (>0.5‰, BAC) vs. less than 0.5‰ alcohol (no BAC). Injury severity, vital signs, complications, mortality, and systemic interleukin (IL)-6 levels were prospectively determined, and BAC was quantified. According to ISS, AIS-head, age, and sex, we performed matched-pair analysis. Results: A total of 101 TBI patients were included. Of them 74 patients were dedicated to no BAC group and 27 to BAC group. ISS was significantly higher in the no BAC group. Positive BAC group required significantly less packed red blood cells and fresh frozen plasma ( P < 0.05). Shorter ICU stays were found in BAC-positive patients. Inhospital complications, including single/multiple organ failure, systemic inflammatory response syndrome, sepsis, pneumonia, and acute respiratory distress syndrome, showed no significant differences. Systemic IL-6 levels and leukocyte counts (IL-6: 65.0 ± 8.0 vs. 151.8 ± 22.3; leukocytes: 10.2 ± 0.9 vs. 13.2 ± 0.8, both P < 0.05) were significantly lower in BAC-positive patients. Matched-pair analysis was performed with 27 pairs. No significant differences in transfusions were monitored after matching. However, lowered systemic IL-6 levels and leukocyte counts in the BAC group were also detected after matching, indicating that this effect is ISS-independent. Conclusions: This study shows that positive BAC in TBI patients is associated with lower systemic IL-6 levels and leukocyte numbers, indicating that positive BAC may have immunosuppressive effects in this cohort of patients compared with TBI patients who were not alcohol intoxicated.